Correlation between Glasgow coma scale on admission and clinical outcome of patients with unilateral chronic subdural hematoma after surgery (Bangabandhu Sheikh Mujib Medical University Journal, 2017)
This study was undertaken to determine the influence of Glasgow coma scale (GCS) on admission on clinical outcome of patients with unilateral chronic subdural hematoma after surgery. A cross- sectional study was conducted on 33 consecutive patients, among them 28 were male, 5 were female with GCS 6 to 15. 19 patients out of 22 who had GCS 14-15 had favorable GOS at 24 hours as compared to 2 out of 7 in GCS 9-13 group and none in GCS ?8 group. All patients (22 out of 22) had favorable GOS at the time of discharge in GCS 14-15 group while 8 out of 9 had favorable GOS in GCS 9-14 group and 1 out of 2 patients had favorable GOS in GCS ?8 group. Chi square test showed significant difference in outcome between 14-15, 9-13 and ?8 GCS groups (p values 0.001, 0.015, 0.013 respectively). In conclusion, clinical outcome of patients with unilateral chronic subdural hematoma depends on Glasgow coma scale on admission.